Assessment of supracrestal tissue attachment variation in patients with chronic periodontitis before and after treatment: A clinical-radiographic study - Saquib, Shahabe; Anoop, Gore; Dani, Nitin; Ashfaque, Yaqoob; Khan, Abdul Ahad; Attar, Nilofer; Al-qahatani, Saad (Vojnosanitetski pregled, 2020)
Background/Aim. Healthy periodontium comprises the dento-gingival junction. Periodontal disease starts to appear when the integrity of the junctional epithelium is disturbed. Assessment of the supracrestal tissue attachment (SCTA) is essential because there is a frequent need for restoration or prosthesis after periodontal surgical and non-surgical therapy. The aim of the present study was to evaluate the SCTA variations in a patients with chronic periodontitis before and after treatment. Methods. Thirty systemically healthy patients with periodontitis were enrolled in the study. Fifteen patients were subjected to scaling and root planing and 15 to open flap debridement. Radiographic and clinical findings of the SCTA were assessed before and after treatment at 3-month and 6-month intervals. Results. Comparison between clinical and radiographic findings of the SCTA showed a significant difference in patients with periodontitis (p < 0.05). This difference was not significant after treatment of patients with shallow pockets with scaling and root planing (p > 0.05), but showed a significant difference in patients with moderate pockets treated by open flap debridement (p < 0.05). Conclusion. Progression in periodontal disease causes a reduction in the SCTA dimension, which regains its original dimensions after periodontal therapy. It takes around 3 months for the shallow pockets to regain the supracrestal tissue attachment to the original dimension when treated by scaling and root planing, whereas moderate pockets regain it after 6 months when treated with open flap debridement.